Program Pengembangan Karakter dan Variasi Metode Pembelajaran Digital sebagai Upaya Peningkatan Literasi Siswa - Salsabila, Dio Ivanca; Azzahra, Mutia; Fatimah, Alida Zia; Sari, Rafika (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
This Community Service Program (PkM) aims to enhance the quality of education at SDN Medalkrisna 01 through three main activities: Literacy Eradication, Mini Cinema, and STEM-Based Learning. The Literacy Eradication program provides reading and writing guidance to students with literacy difficulties using phonemic techniques and progressive writing exercises. The Mini Cinema program is designed to raise students' awareness of the three major educational sins (bullying, intolerance, and sexual violence) through educational film screenings followed by interactive discussions. Meanwhile, STEM-Based Learning is implemented in science lessons through hands-on experiments, such as making churned ice cream, to understand the concept of phase changes in matter. The results of these programs show improvements in students’ literacy skills, awareness of the negative impacts of bullying, and increased interest in science and technology. Additionally, positive feedback from students and teachers indicates the effectiveness of the program in creating a more inclusive and innovative learning environment.